The Hemagglutinin-Neuraminidase (HN) Head Domain and the Fusion (F) Protein Stalk Domain of the Parainfluenza Viruses Affect the Specificity of the HN-F Interaction - Tsurudome, Masato; Ohtsuka, Junpei; Ito, Morihiro; Nishio, Machiko; Nosaka, Tetsuya (Frontiers in Microbiology, 2018)
Membrane fusion by the parainfluenza viruses is induced by virus-specific functional interaction between the attachment protein (HN) and the fusion (F) protein. This interaction is thought to be mediated by transient contacts between particular amino acids in the HN stalk domain and those in the F head domain. However, we recently reported that replacement of specified amino acids at or around the dimer interface of the HN head domain remarkably affected the F protein specificity. We then intended to further investigate this issue in the present study and revealed that the HPIV2 HN protein can be converted to an SV41 HN-like protein by substituting at least nine amino acids in the HPIV2 HN head domain with the SV41 HN counterparts in addition to the replacement of the stalk domain, indicating that specified amino acids in the HN head domain play very important roles in determining the specificity of the HN-F interaction. On the other hand, we previously reported that the PIV5 F protein can be converted to an SV41 F-like protein by replacing 21 amino acids in the head domain of the PIV5 F protein with those of the SV41 F protein. We then intended to further investigate this issue in the present study and found that replacement of 15 amino acids in the stalk domain in addition to the replacement of the 21 amino acids in the head domain of the PIV5 F protein resulted in creation of a more SV41 F-like protein, indicating that specified amino acids in the F stalk domain play important roles in determining the specificity of the HN-F interaction. These results suggest that the conformations of the HN stalk domain and the F head domain are dependent on the structures of the HN head domain and the F stalk domain, respectively. Presumably, the conformations of the former domains, which are considered directly involved in the HN-F interaction, can be modified by subtle changes in the structure of the latter domains, resulting in an altered specificity for the interacting partners.